Analisis dan Proyeksi Kebutuhan Beberapa Komoditas Tanaman Pangan menggunakan Pendekatan Sistem Dinamis untuk Memenuhi Kebutuhan Pangan di Kabupaten Manokwari - Arif Faisol; Siti Asfihana Rahmawati; Hostalige Hutasoit (Universitas Muhammadiyah Sorong, 2023)
Food is one of the fundamental requirements that must be fulfilled for everyone. The Food Balance Sheet (FBS) is one of the tools used to describe the food situation of a region. This study aims to analyze and project the requirement of food crops in Manokwari using a dynamic system modeling, i.e. paddy, soybeans, corn, peanuts, green beans, cassava, and sweet potatoes. Generally, this research consists of 4 (four) main stages, i.e. data inventory, data analysis, system dynamic model design, and projection of the requirement of food crops until 2050. The research showed that in 2022 some food crops production is in deficit, i.e. rice, soybeans, and green beans. Furthermore, corn, peanuts, cassava, and sweet potatoes are surplus. One of the solutions to supply food consumption in Manokwari Regency until 2050 is increasing food crop production through the expansion of food cropland and the use of superior varieties. In addition, increasing the Crop Index (CI) of rice plants from 2 times a year to 3 times a year is an alternative solution to increase rice production due to limited agricultural land provided by the government.